K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(=2\cdot sin53^0\cdot cos53^0+1-3=sin106^0-2\)

17 tháng 8 2018

ta có : \(M=2cot37.cot53+sin^228\dfrac{3tan54}{cot36}+sin^262\)

\(=2.cot37.cot\left(90-37\right)+sin^228\dfrac{3tan54}{cot\left(90-54\right)}+sin^262\)

\(=2.cot37.tan37+sin^228\dfrac{3tan54}{tan54}+sin^262\)

\(=2+3sin^228+sin^262=2+2sin^228+sin^228+sin^2\left(90-28\right)\)

\(=2+2sin^228+sin^228+cos^228=3+2sin^228\)

27 tháng 9 2018

a) 1 + tan22 a =1 +(\(\dfrac{sina}{cosa}\))2 =\(\dfrac{sina+cosa}{cos^2a}\)=\(\dfrac{1}{cos^2a}\)

b) 1 + cot2 a= 1 +(\(\dfrac{cosa}{sina}\))2 = \(\dfrac{cosa+sina}{sin^2a}\)=\(\dfrac{1}{sin^2a}\)

c) tan2 a (2 sin2a + 3 cos2 a - 2)

=tan2 a[cos2 a +2 (\(sina^2+cos^2a\))-2 ]

=\(\dfrac{sin^2a}{cos^2a}\)×\(cos^2a=sin^2a\)

b: \(1+cot^2a=1+\left(\dfrac{cosa}{sina}\right)^2=\dfrac{1}{sin^2a}\)

c: \(=tan^2a\left[2\left(1-cos^2a\right)+3cos^2a-2\right]\)

\(=tan^2a\left[cos^2a\right]\)

\(=\dfrac{sin^2a}{cos^2a}\cdot cos^2a=sin^2a\)

AH
Akai Haruma
Giáo viên
27 tháng 6 2018

Hỏi đáp Toán

AH
Akai Haruma
Giáo viên
27 tháng 6 2018

Hỏi đáp Toán

16 tháng 10 2019

Ta có : \(\cot\left(37\right)=\tan\left(53\right)\) ,\(\sin^2\alpha+\cos^2\alpha=1,\tan\alpha\cdot\cot\alpha=1\)

\(sin\left(28\right)=\cos\left(62\right)\)

\(\Leftrightarrow sin^2\left(28\right)=\cos^2\left(62\right)\)

\(\cot\left(36\right)=\tan\left(54\right)\)

Đề : \(\cot\left(37\right)\cdot\cot\left(53\right)+\sin^2\left(28\right)-\frac{3\cdot\tan\left(54\right)}{\cot\left(36\right)}+sin^2\left(62\right)\)

\(=\tan\left(53\right)\cdot\cot\left(53\right)+\cos^2\left(62\right)-\frac{3\cdot\tan\left(54\right)}{\tan\left(54\right)}+\sin^2\left(62\right)\)

\(=\)\(\tan\left(53\right)\cdot\cot\left(53\right)+\cos^2\left(62\right)+\sin^2\left(62\right)-\frac{3\cdot\tan\left(54\right)}{\tan\left(54\right)}\)

\(=1+1-3\)

\(=-1\)